Communication, Information Exchange, and Service Delivery Mobile Platforms and Agricultural Success among Dodoma and Singida Sunflower Farmers in Tanzania - Shuma, Zarina Ally; Thomas, Tumsifu Elly; Mbamba, Ulingeta Obadia (University of Dar es Salaam Library Journal, 2026)
This paper presents the findings of a study that examined the impact of mobile platform capabilities in terms of communication, information sharing and service delivery on agricultural success among sunflower farmers, grounded in Human Capital Theory and Innovation Diffusion Theory. It highlights the roles farmers’ innovativeness, technical skills, and personal relationships play in driving agricultural success. Survey data collected from Dodoma and Singida sunflower farmers were analysed using Structural Equation Modelling (PLS-SEM). The study found that the three aspects of mobile platform capabilities (innovation, technical skills, and personal relations) positively and significantly influence the success of sunflower farmers. These results suggest that mobile technologies enhance farmers’ ability to innovate, improve skills, and foster stronger networks, all of which contribute to greater agricultural success. As such, farmers should receive further support and training to leverage mobile platforms effectively. For policymakers and practitioners, the findings underscore the importance of integrating mobile technologies into agricultural policies and development initiatives to boost productivity.